The Influence of Company Finances on Receiving Going Concern Audit Opinions : Study of Mining Companies Listed on The IDX in 2016-2020 - Gantina Tigusti; Roro Endah Kumalasari (Jurnal Computech & Bisnis (e-Journal), 2023)
This study aims to determine the effect of the company's financial condition on the acceptance of going concern audit opinions in mining sector companies listed on the IDX in 2016 – 2020. The research method used in this study is a descriptive method with a quantitative approach. The population used in this study are mining companies listed on the IDX in 2016 – 2020, totaling 49 companies. The sampling technique used was purposive sampling, totaling 24 companies based on predetermined criteria. The data used in this study is secondary data in the form of the company's annual report. The results of the analysis of this study are (1) the company's financial condition has a negative effect on acceptance of going-concern audit opinion with a significant level of 0.001 <0.005, (2) the results of data processing through logistic regression show Y = -1.035 - 1.147, which means that if the financial condition is increased by one - unit, the going concern audit opinion value will likely decrease by -1.147.